2022
DOI: 10.1111/jopr.13515
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Accuracy of Lithium Disilicate Full‐Coverage Single Crowns Made by Direct and Indirect Digital or Conventional Workflows: A Systematic Review and Meta‐Analysis

Abstract: Purpose Several studies have compared digital intraoral scanners and conventional impressions. The accuracy of these two methods in terms of marginal accuracy of lithium disilicate crowns is not well‐established, yet. The purpose of this study was to systematically review available publications on marginal fit of single‐unit, full‐coverage, tooth‐supported lithium disilicate restorations. Methods Pubmed, Web of Science, Cochrane, EMBASE, and Scopus were electronically searched along with a manual search. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
0
10
0
3
Order By: Relevance
“…16,[19][20][21] Complete digital workflows for fabricating tooth-and implantsupported crowns and short span fixed dental prostheses obtain similar marginal and internal discrepancies compared with conventional methods. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] The challenge today remains to incorporate IOSs into complete digital workflows for fabricating complete dentures 29 and Kennedy Class I and II removable partial dentures. 30 Published studies have shown that intraoral digital scans can accurately digitized edentulous areas with firm attached tissue and mucosa, but capturing areas with mobile tissue by using an IOS is challenging, regardless of the scanning technology and system elected.…”
Section: Ios Technology and Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…16,[19][20][21] Complete digital workflows for fabricating tooth-and implantsupported crowns and short span fixed dental prostheses obtain similar marginal and internal discrepancies compared with conventional methods. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] The challenge today remains to incorporate IOSs into complete digital workflows for fabricating complete dentures 29 and Kennedy Class I and II removable partial dentures. 30 Published studies have shown that intraoral digital scans can accurately digitized edentulous areas with firm attached tissue and mucosa, but capturing areas with mobile tissue by using an IOS is challenging, regardless of the scanning technology and system elected.…”
Section: Ios Technology and Systemmentioning
confidence: 99%
“…Complete digital workflows for fabricating tooth‐ and implant‐supported crowns and short span fixed dental prostheses obtain similar marginal and internal discrepancies compared with conventional methods 21–35 . The challenge today remains to incorporate IOSs into complete digital workflows for fabricating complete dentures 29 and Kennedy Class I and II removable partial dentures 30 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations